Identification of the current path for a conductive molecular wire on a tripodal platform. Issue 20 (10th May 2016) - Karimi, M. A.; Bahoosh, S. G.; Valášek, M.; Bürkle, M.; Mayor, M.; Pauly, F.; Scheer, E.
Abstract : We present charge transport measurements and calculations and outline the chemical synthesis route for a new tripodal platform based on a rigid 9, 9′-spirobifluorene equipped with a phenylene-ethynylene wire. Abstract : We present the chemical synthesis as well as charge transport measurements and calculations for a new tripodal platform based on a rigid 9, 9′-spirobifluorene equipped with a phenylene-ethynylene wire. The transport experiments are performed with the help of the low-temperature mechanically controlled break junction technique with gold electrodes. By combining experimental and theoretical investigations of elastic and inelastic charge transport, we show that the current proceeds through the designated molecular wire and identify a binding geometry that is compatible with the experimental observations. The conductive molecular wire on the platform features a well-defined and relatively high conductance of the order of 10 −3 G 0 despite the length of the current path of more than 1.7 nm, demonstrating that this platform is suitable to incorporate functional units like molecular switches or sensors.